2012
DOI: 10.2739/kurumemedj.59.5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Masseter Muscle Form and Occlusal Supports of Remaining Teeth

Abstract: To chew, it is necessary to maintain harmony between the masseter muscle and other organs. Various studies have been conducted on the masseter muscle, but none has examined the relationships among masseter muscle form, occlusal support of remaining teeth, and maxillofacial morphology. Thus, we conducted the present study using cadavers donated to anatomy practice. After the masseter muscle was extracted, its length, width, thickness, and volume were measured; histological observations were conducted; and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
1
19
0
2
Order By: Relevance
“…For CD wearers, a pattern of consuming soft foods leads to lower masticatory effort and explains reduced masseter electrical activity . A cadaveric study showed that loss of occlusal support is also associated with atrophy of chewing muscles, primarily the masseters. One in vivo rat study showed that reduced diet consistency and quality indirectly contributes to deterioration in masticatory muscle function and changes in skull form during growing .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For CD wearers, a pattern of consuming soft foods leads to lower masticatory effort and explains reduced masseter electrical activity . A cadaveric study showed that loss of occlusal support is also associated with atrophy of chewing muscles, primarily the masseters. One in vivo rat study showed that reduced diet consistency and quality indirectly contributes to deterioration in masticatory muscle function and changes in skull form during growing .…”
Section: Introductionmentioning
confidence: 99%
“…Prosthetic rehabilitation seems to play a crucial role in maintaining masticatory function and preventing muscle atrophy . Tetsuka et al . reported that CD wearers have greater masseter muscle thickness compared to edentulous persons who do not use CDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are changes in the masticatory muscles that accompany partial as well as complete loss of the teeth. For example, mass of the masseter muscle decreases with increasing loss of teeth [25]. This is attributed to the associated reduction in mandibular stability and masticatory function with progressive loss of teeth, and it is possible that similar reductions occur in the size and strength of other, submental muscles that contribute to both mastication and airway stability during sleep [26].…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of occlusal support protects against atrophy of masseter muscle fiber thickness and volume, especially in the premolar region [25]. Moreover, dentures restore the vertical dimension of occlusion, lower facial height, retropharyngeal and posterior airway spaces, and peak inspiratory flow rates [11, 28].…”
Section: Discussionmentioning
confidence: 99%